Carbon pricing and green growth: a systematic review of policy effectiveness, design, and equity - Nii-Okai, Enoch; Yeboah, Alfred; Xonu, Emmanuel; Olayode, Ayodeji; Osarodion, Efe; Wiafe, Gopal; Ackah, Albert; Enobakhare, Benjamin (Journal of Environment Climate and Ecology, 2025)
Climate change constitutes a major market failure because greenhouse gas emissions are not priced to reflect their social costs. Carbon pricing has become a central policy instrument, yet its effectiveness varies across contexts. This review evaluates the performance of carbon taxes and emissions trading systems by examining their environmental, economic, and equity outcomes. The analysis applies a systematic review framework covering peer-reviewed studies, meta-analyses, and international policy assessments published between 2008 and 2025. Evidence is synthesized across three dimensions: emissions reductions, innovation and structural change, and distributional impacts. The literature consistently shows that carbon pricing reduces emissions when price signals are strong, credible, and increase predictably over time. Jurisdictions with rising tax schedules or progressively tightening emissions caps achieve the most durable mitigation. Carbon pricing also stimulates low-carbon innovation and supports long-term structural change, especially when combined with complementary policies. Distributional outcomes vary, but equity improves significantly when revenues are returned through rebates or tax reductions. Overall effectiveness depends more on design quality and policy coherence than on whether pricing is delivered through taxes or trading systems. Credible long-term price paths, broad sectoral coverage, transparent governance, and equitable revenue use are essential conditions for achieving sustained environmental and socio-economic benefits.
Keywords: Carbon tax; Emissions trading; Equity (law); Greenhouse gas; Market failure; Revenue; Tax revenue; dept.egm